2014
DOI: 10.1161/circgenetics.114.000621
|View full text |Cite
|
Sign up to set email alerts
|

Family History of Myocardial Infarction and Cause-Specific Risk of Myocardial Infarction and Venous Thromboembolism

Abstract: Background-A family history of myocardial infarction (FHMI) has been shown to increase the risk of venous thromboembolism (VTE). The mechanism underlying the association remains unclear. Therefore, we aimed to determine the risks of MI and VTE by FHMI using a cause-specific model and to explore whether atherosclerotic risk factors could explain the association between FHMI and VTE in a population-based cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
22
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 43 publications
(64 reference statements)
8
22
0
1
Order By: Relevance
“…Different VTE manifestations and varicose veins also partially share familial susceptibility 2. However, CHD and ischaemic stroke do not share strong familial susceptibility with VTE in two nationwide family studies,4 5 though an association between VTE and MI has been reported in the Tromsø study 3 6. Our study adds to these previous findings that indicated that most arterial thromboembolic manifestations do not share familial susceptibility with VTE.…”
Section: Discussionmentioning
confidence: 39%
“…Different VTE manifestations and varicose veins also partially share familial susceptibility 2. However, CHD and ischaemic stroke do not share strong familial susceptibility with VTE in two nationwide family studies,4 5 though an association between VTE and MI has been reported in the Tromsø study 3 6. Our study adds to these previous findings that indicated that most arterial thromboembolic manifestations do not share familial susceptibility with VTE.…”
Section: Discussionmentioning
confidence: 39%
“…In an attempt to determine the impact of cardiovascular risk factors, including family history of myocardial infarction, on the incidence of VTE, investigators from Norway extracted data from more than 21 000 subjects, aged 25-96 years, who had been enrolled in a prospective, population-based study (the Tromsø Study) [35,36] . In multivariable analysis, family history of myocardial infarction was significantly associated not only with an increased risk of infarction but also of total VTE (HR, 1.27; 95% CI 1.01-1.60) and unprovoked VTE (HR, 1.46; 95% CI: 1.03-2.07.…”
Section: Is Atherosclerosis Predictive Of Vte?mentioning
confidence: 99%
“…A study [21], on the behalf of GISSI-EFRIM, investigates the association between family history of MI and risk of AMI [22][23][24][25]. These mentioned studies have reported that Family history of heart disease was a significant and independent risk factor of MI.…”
Section: Discussionmentioning
confidence: 99%